The Impact of Ischemia Assessed by Magnetic Resonance on Functional, Arrhythmic, and Imaging Features of Hypertrophic Cardiomyopathy - Aguiar Rosa, Sílvia; Thomas, Boban; Fiarresga, António; Papoila, Ana Luísa; Alves, Marta; Pereira, Ricardo; Branco, Gonçalo; Cruz, Inês; Rio, Pedro; Baquero, Luis; Ferreira, Rui Cruz; Mota Carmo, Miguel; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: The aim of the study is to investigate the association between the degree of ischemia due to coronary microvascular dysfunction (CMD) and the left ventricular (LV) tissue characteristics, systolic performance, and clinical manifestations in hypertrophic cardiomyopathy (HCM). Methods and Results: This prospective study enrolled 75 patients with HCM without obstructive epicardial coronary artery disease. Each patient underwent cardiovascular magnetic resonance (CMR) including parametric mapping, perfusion imaging during regadenoson-induced hyperemia, late gadolinium enhancement (LGE) and three-dimensional longitudinal, circumferential, and radial strains analysis. Electrocardiogram, 24-h Holter recording, and cardiopulmonary exercise testing (CPET) were performed to assess arrhythmias and functional capacity. In total, 47 (63%) patients were men with the mean age of 54.6 (14.8) years, 51 (68%) patients had non-obstructive HCM, maximum wall thickness (MWT) was 20.2 (4.6) mm, LV ejection fraction (LVEF) was 71.6 (8.3%), and ischemic burden was 22.5 (16.9%) of LV. Greater MWT was associated with the severity of ischemia (β-estimate:1.353, 95% CI:0.182; 2.523, p = 0.024). Ischemic burden was strongly associated with higher values of native T1 (β-estimate:9.018, 95% CI:4.721; 13.315, p < 0.001). The association between ischemia and LGE was significant in following subgroup analyses: MWT 15–20 mm (β-estimate:1.941, 95% CI:0.738; 3.143, p = 0.002), non-obstructive HCM (β-estimate:1.471, 95% CI:0.258; 2.683, p = 0.019), women (β-estimate:1.957, 95% CI:0.423; 3.492, p = 0.015) and age <40 years (β-estimate:4.874, 95% CI:1.155; 8.594, p = 0.016). Ischemia in ≥21% of LV was associated with LGE >15% (AUC 0.766, sensitivity 0.724, specificity 0.659). Ischemia was also associated with atrial fibrillation or flutter (AF/AFL) (OR-estimate:1.481, 95% CI:1.020; 2.152, p = 0.039), but no association was seen for non-sustained ventricular tachycardia. Ischemia was associated with shorter time to anaerobic threshold (β-estimate: −0.442, 95% CI: −0.860; −0.023, p = 0.039). Conclusion: In HCM, ischemia associates with morphological markers of severity of disease, fibrosis, arrhythmia, and functional capacity.